The release and catabolism of ferulic acid in plant cell wall by rumen microbes: A review - Yan-Lu Wang; Wei-Kang Wang; Qi-Chao Wu; Hong-Jian Yang (Animal Nutrition, 2022)
Ferulic acid (FA) is one of the most abundant hydroxycinnamic acids in the plant world, especially in the cell wall of grain bran, in comparison with forage and crop residues. Previous studies noted that FA was mainly linked with arabinoxylans and lignin in plant cell walls in ester and ether covalent forms. After forages were ingested by ruminant animals or encountered rumen microbial fermentation in vitro, these cross-linkages form physical and chemical barriers to protect cell-wall carbohydrates from microbial attack and enzymatic hydrolysis. Additionally, increasing studies noted that FA presented some toxic effect on microbial growth in the rumen. In recent decades, many studies have addressed the relationships of ester and/or ether-linked FA with rumen nutrient digestibility, and there is still some controversy whether these linkages could be used as a predicator of forage digestibility in ruminants. The authors in this review summarized the possible relationships between ester and/or ether-linked FA and fiber digestion in ruminants. Rumen microbes, especially bacteria and fungi, were found capable of breaking down the ester linkages within plant cell walls by secreting feruloyl and p-coumaroyl esterase, resulting in the release of free FA and improvement of cell wall digestibility. The increasing evidence noted that these esterases secreted by rumen microbes presented synergistic effects with xylanase and cellulase to effectively hydrolyze forage cell walls. Some released FA were absorbed through the rumen wall directly and entered into blood circulation and presented antioxidant effects on host animals. The others were partially catabolized into volatile fatty acids by rumen microbes, and the possible catabolic pathways discussed. To better understand plant cell wall degradation in the rumen, the metabolic fate of FA along with lignin decomposition mechanisms are needed to be explored via future microbial isolation and incubation studies with aims to maximize dietary fiber intake and enhance fiber digestion in ruminant animals.